Diltiazem is a useful and effective medication for reversal of coronary artery spasm-induced complete atrioventricular block: A case report - Zhang, Jin; Liu, Li; Liu, Chengwei; Han, Min; Xu, Chengyi; Qiu, Rujie (Frontiers in Cardiovascular Medicine, 2023)
Coronary artery spasm (CAS) is characterized by reversible diffuse or focal vasoconstriction, a phenomenon that plays an important role in the pathogenesis of ischemic heart disease. Fatal arrhythmias, such as ventricular tachycardia/fibrillation and complete atrioventricular block (AV-B), are very common in patients with CAS. Nondihydropyridine calcium channel blockers (CCBs) such as diltiazem were recommended as first-line medications for treating and preventing CAS episodes. However, its use remains controversial in CAS patients with AV-B as this type of CCB can also cause AV-B itself. Here, we present the use of diltiazem in a patient with complete AV-B caused by CAS. The patient's chest pain was rapidly relieved, and complete AV-B was promptly restored to sinus rhythm following the administration of intravenous diltiazem without any adverse effects. In this report, we highlight the useful and effective application of diltiazem for treating and preventing complete AV-B caused by CAS.